Pengaruh Digital Fundraising Terhadap Pendayagunaan Dana Zakat di Yayasan Kesejahteraan Madani (Yakesma) Sumatera Selatan - Tuti Awaliyah; Candra Darmawan; Hasril Atieq Pohan (ScidacPlus, 2023)
The purpose of this study is to determine the effect of digital fundraising on the utilization of zakat funds. This research method uses quantitative methods using a causal associative approach. Sources of data used are primary data and secondary data, data collection techniques using observation methods, questionnaires / questionnaires and documentation. The data analysis technique used is a simple linear regression analysis technique. The results of this study indicate that good and regular digital fundraising can increase a great influence on zakat management and is very much needed to run zakat programs at YAKESMA SUMSEL. With the existence of digital fundraising, it is able to provide great benefits in the management of zakat because it is a means to increase zakat utilization activities in carrying out the zakat program at YAKESMA, along with the results of data processing with the SPSS version 25.0 program which obtained a t count > t table of (21,587 > 1,662) and a significance value of 0.000 <0.05, it can be said that there is an Influence of Digital Fundraising on the Utilization of Zakat Funds, this is also the magnitude of the coefficient of determination or R square of 0.840 (84%) it can be concluded that in this study the variable Digital fundraising (X ) has an effect on the Utilization of Zakat Funds (Y) by 84% and the remaining 16% is influenced by other variables outside the variables studied. It is hoped that the YAKESMA SUMSEL zakat institution and the community can apply the use of digital fundraising so that it can facilitate the optimal management process so that it is able to achieve the goal of empowering zakat.